Outcomes of interval cholecystectomy after EUS-guided gallbladder drainage: a systematic review and meta-analysis - Arayakarnkul, Suchapa; Blomker, Jacquelin; Seid, Amir Sultan; Afraz, Iman; Theis-Mahon, Nicole; Wilson, Natalie; Karna, Rahul; Bilal, Mohammad (Gastrointestinal endoscopy, 2025)
Cholecystectomy (CCY) is considered the criterion standard intervention for acute cholecystitis (AC). However, EUS-guided gallbladder drainage (EUS-GBD) can be performed in patients unfit for surgery. Interval CCY after EUS-GBD is typically not performed because the formation of a cholecystoenteric fistula increases the technical complexity of CCY. We conducted a systematic review and meta-analysis to determine the outcomes of interval CCY after EUS-GBD. We conducted a literature search of multiple electronic databases for studies reporting on outcomes of interval CCY after EUS-GBD. Primary outcomes were pooled proportions of technical success of interval CCY and surgical techniques (rate of open, laparoscopic, and conversion from laparoscopic to open). The secondary outcome was adverse events (AEs). A meta-analysis of proportions was performed using the random-effects model. The I2 statistic was used to assess heterogeneity. Of 1001 citations, 15 studies with 707 patients were included. The pooled proportion of successful interval CCY was 32.9% (95% CI, 11.8-53.9; I2 = 99%). Surgical techniques included laparoscopic CCY in 76.2% (95% CI, 61.5-91.0; I2 = 82%), open CCY in 14.5% (95% CI, 4.2-24.8; I2 = 82%), and conversion from laparoscopic to open CCY in 14% (95% CI, 4.1-23.8; I2 = 77%). The pooled proportion of overall AEs was 13.2% (95% CI, 4.3-22.1; I2 = 61%), including postoperative infection in 7.6% (95% CI, 0.7-14.6; I2 = 65%). There was no procedure-related mortality. Our study demonstrates that interval CCY is technically feasible and safe after EUS-GBD. Endoscopists should still consider the local surgical expertise and recommendations before performing EUS-GBD in patients who could eventually become surgical candidates afterward. [Display omitted]